Isolation and Selection of Bacillus spp. as Candidate Probiotics for Use in Chickens - Adawiah, Adilah; Wiryawan, Komang Gede; Meryandini, Anja (UI Scholars Hub, 2025)
The growth rate of chickens can be improved by using probiotics as alternatives to antibiotics. Bacillus spp. as probiotics are particularly beneficial due to ability to form spores, which remain stable as commercial products over extended periods. This study aimed to isolate and select Bacillus spp. from Jasinga soil as probiotic candidates for chickens. A total of 15 isolates obtained of these, 12 were identified as Bacillus spp based on microscopic observations and screening test including ascertaining hemolysis, protease, amylase, and cellulase activities. Only six isolates exhibited gamma hemolysis and the ability to hydrolyze proteins, starch, and cellulose. Isolates BTJ1.1, 1.2, 1.4, and 2.3 poliferated in 0.3% bile salts. BTJ1.1, 1.2 and 2.3 also exhibited antimicrobial activity and sensitivity to amoxicillin, tetracycline, and rifampicin. BTJ1.1 and 2.3 were highly hydrophobic, a key probiotic trait. 16S rRNA gene sequence analysis revealed that BTJ1.1 and 2.3 were >99% similar to B. amyloliquefaciens strain B54 and B. subtilis strain ASI3, respectively, highlighting their potential as probiotics.